The Effect of the Maqashid Sharia Index on Financial Sustainability: Evidence from Islamic Rural Bank in Central Java - Muhammad Naufal Majid; Purbayu Budi Santoso; Putri Rizka Citaningati (Faculty of Economics UIN Maulana Malik Ibrahim Malang, 2026)
The study aims to provide empirical evidence on the effect of the Maqashid Sharia Index (MSI) on the Financial Sustainability Ratio (FSR) at Islamic Rural Banks in Central Java from 2020 to 2023. This study employs panel data regression and purposive sampling techniques across 11 Islamic Rural Banks. The analysis conducted in this study used Chow, Hausman, and Lagrange Multiplier tests to determine the best model. The results of this study indicate that individual education (tahdhib al-fard) and welfare (jalb al-maslahah) have a significant positive effect on FSR, while upholding justice (iqamah al-adl) has no significant effect. The financial sustainability is also determined by social and spiritual responsibility. This key finding emphasizes that the non-financial dimensions of Sharia are a crucial driver of the sustainability of Sharia entities. The implications of this study underscore the need for management and regulators of Islamic Rural Banks to strengthen education, training, and zakat distribution, prioritizing investments in human resource development and zakat-based welfare activities to improve the financial sustainability of Islamic Rural Banks in the future. The limitations of this study include a sample scope limited to 11 Islamic Rural Banks in Central Java.